Determination of trace concentrations of simple phenols in ambient PM samples. (September 2022) - Ogrizek, Monika; Kroflič, Ana; Šala, Martin
Abstract: Phenols are hazardous, but yet ubiquitous in the environment, including in atmospheric aerosols due to combustion emissions. There, phenols are subjected to secondary transformations, producing even more toxic nitrophenolic air pollutants. However, primary simple phenols, i.e. those containing only hydroxyl, methyl and methoxy substituents are not easy to detect. Trace concentrations, semi-volatile character and poorly ionizable functional groups prevent us from their determination by the most common analytical techniques, such as gas and liquid chromatography with mass spectrometric detection (GC/LC-MS). Here, we present a new derivatization method for MS/MS detection with positive ion electrospray ionization (+ESI-MS/MS) of simple phenols in atmospheric particulate matter (PM) extracts. The method is sensitive, selective, and robust, and requires no sample concentration step, which is critical due to the volatile character of the target analytes. After derivatization with dansyl chloride, phenol, catechol, cresols and guaiacol were detected in urban PM samples from Ljubljana, Slovenia. This method finally enables to study the abundance of primary phenols in atmospheric PM from different sources, which will improve understanding of secondary aerosol (trans)formation pathways and allow for more targeted mitigation strategies in respect to airborne phenolic pollutants. Graphical abstract: Image 1 Highlights: Phenol dansylation improves ionization and enables LC-MS analysis. Optimal reaction and measuring parameters provide very low limits of detection. Phenol, catechol, guaiacol and cresol are determined in ambient particulate matter. Concentrations of simple phenols in particulate matter are low, peaking in winter. Simple phenols can be precursors to toxic secondary aerosols ( e.g. nitrophenols).